Advanced endoscopic imaging for diagnosis of inflammatory bowel diseases: Present and future perspectives. Issue 4 (19th February 2018) - Sivanathan, Visvakanth; Tontini, Gian Eugenio; Möhler, Markus; Galle, Peter R.; Neumann, Helmut
Abstract : Crohn's disease and ulcerative colitis are chronic inflammatory bowel diseases (IBD) causing severe damage of the luminal gastrointestinal tract. Differential diagnosis between both disease entities is sometimes awkward requiring a multifactorial pathway, including clinical and laboratory data, radiological findings, histopathology and endoscopy. Apart from disease diagnosis, endoscopy in IBD plays a major role in prediction of disease severity and extent (i.e. mucosal healing) for tailored patient management and for screening of colitis‐associated cancer and its precursor lesions. In this state‐of‐the‐art review, we focus on current applications of endoscopy for diagnosis and surveillance of IBD. Moreover, we will discuss the latest guidelines on surveillance and provide an overview of the most recent developments in the field of endoscopic imaging and IBD.